Historic Lake Drainage on the Western Arctic Coastal Plain in Northern Alaska from Remote Sensing Datasets, 1955-2017 - Jones, Benjamin; Arp, Christopher; Grosse, Guido; Nitze, Ingmar; Lara, Mark; Whitman, Matthew; Farquharson, Louise; Kanevskiy, Mikhail; Parsekian, Andrew; Breen, Amy; Ohara, Nori; Rangel, Rodrigo; et al. (Arctic Data Center, 2019)
We identified all lakes larger than 10 hectares (ha) that drained completely or partially (greater than 25 %) between 1955 and 2017 using historical (original) USGS topographic maps and aerial photography (1955) and Landsat Imagery (circa 1975, circa 2000, and annually since 2000). For each lake drainage event, we inferred the drainage mechanism and categorized the drainage pathway based on known lake drainage mechanisms using interpretation of high-resolution remote sensing data and field observations.